Challenges and opportunities for electric aircraft thermal management. Issue 6 (30th September 2014) - Freeman, Jeffrey; Osterkamp, Philip; Green, Michael; Gibson, Andrew; Schiltgen, Benjamin
Abstract : Purpose: – The purpose of this article is to provide an outline of the challenges of thermal management for more-electric, hybrid-electric and all-electric aircraft, and to notionally discuss potential solutions. Design/methodology/approach: – A code algorithm was developed to facilitate architecture-level analysis of the coupled relationship between the propulsion system, the thermal management system, and the takeoff gross weight of aircraft with advanced propulsion systems. Findings: – A variety of coupled relationships between the propulsion and thermal management systems are identified, and their impact on the conceptual design choices for electric aircraft are discussed qualitatively. Research limitations/implications: – This conceptual article merely illuminates some driving factors associated with thermal management. The software is still in its adolescence and is experiencing ongoing development. Practical implications: – Thermal regulation in electric aircraft is shown to be a topic that should be addressed in tandem with propulsion system architecture definition and component selection. High-power electronics are expected to emit an immense amount of heat, and the common avenues of heat dissipation could substantially impact the aircraft's weight, drag and performance. Conversely, strategic management of this waste heat could support subsystems or even produce additional thrust. Social implications: – This paper aims to direct the attention of researchers and designers in the field of hybrid- or all-electric aircraft design toward the challenges and potential benefits of thermal management. Originality/value: – This paper describes a novel conceptual design software and discusses its logic flow and implications.